2023
DOI: 10.3390/biom13030414
|View full text |Cite
|
Sign up to set email alerts
|

GABRG2 Variants Associated with Febrile Seizures

Abstract: Febrile seizures (FS) are the most common form of epilepsy in children between six months and five years of age. FS is a self-limited type of fever-related seizure. However, complicated prolonged FS can lead to complex partial epilepsy. We found that among the GABAA receptor subunit (GABR) genes, most variants associated with FS are harbored in the γ2 subunit (GABRG2). Here, we characterized the effects of eight variants in the GABAA receptor γ2 subunit on receptor biogenesis and channel function. Two-thirds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…As binary α1β3 receptors are commonly expressed at appreciable levels from either injection into oocytes or transfection into mammalian cells of free α, β and γ subunits, 27 , 33 the higher steady-state currents of binary receptors will increase variability whenever free subunits are used. Our results show, that tethered subunits did not significantly affect receptor activation properties or expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…As binary α1β3 receptors are commonly expressed at appreciable levels from either injection into oocytes or transfection into mammalian cells of free α, β and γ subunits, 27 , 33 the higher steady-state currents of binary receptors will increase variability whenever free subunits are used. Our results show, that tethered subunits did not significantly affect receptor activation properties or expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…32 Human studies have demonstrated that pathogenic GABRG2 variants are associated with a spectrum of epilepsies (Figure 2, Table S1). 21,22,24,27 In 2001 the first pathogenic GABRG2 variants were associated with GEFS+, 33 CAE, and FS. 34,35 Based on the initial reports of GABRG2 variants it was generally accepted that missense variants in GABRG2 led to milder phenotypes (CAE and FS) compared to nonsense variants (GEFS+ and DS).…”
Section: Discussionmentioning
confidence: 99%
“…GABRG2 variants are associated with a wide spectrum of epileptic syndromes; from mild epilepsies (such as febrile seizures (FS) and childhood absence epilepsy (CAE)) to more severe epilepsy forms (developmental and epileptic encephalopathies (DEE) such as Dravet syndrome (DS)) 21–24 . We have found 141 (likely) pathogenic GABRG2 variants via ClinVar and Humsavar 25,26 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Automated whole-cell patch clamp recordings were performed at room temperature on HEK293T cells 48 h after transfection with GABA A receptor wt and mutant subunits, according to the manufacturer's standard procedure for the SyncroPatch 384PE (Nanion Technologies, Munich, Germany), previously described [31,32]. Cells at a concentration of 400,000 cells/mL were harvested in suspension in an external solution containing 140 mM NaCl, 2 mM CaCl 2 , 4 mM KCl, 1 mM MgCl 2 , 5 mM glucose, and 10 mM HEPES (pH 7.4, adjusted with NaOH, 298 mOsm).…”
Section: Determination Of Gaba-elicited Responses By Automated Patch ...mentioning
confidence: 99%